The Effect of the Use of the Tradisonal Games "NyumputSarung, Sloppares and Ngakuk Wai" On The Improvement of Social Skills Students of Early Childhood Education in Bandar Lampung - et. al., Laila Maharani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In addition to social content to reintroduce traditional culture, traditional toys can restore children's social skills. The formulation of the problem in this study is how much influence the games of 'nyumput sarong, throwing slippers and ngakukwai' in improving early childhood social skills in Bandar Lampung. This type of research is Pre-Experimental Designs (non-design) research, which is to determine the effect of a treatment in one group, because the research conducted is to determine the effect of traditional games on the development of social skills of early childhood aged 5-6 years. Based on the results of the Mann Whitney Test, it shows that the initial measurement (Pre-Test) and the final measurement (posttest), the value of p = .000 or p <0.05 is obtained, which means that Ha is accepted, which means that there is a significant difference in the level of social skills after ECE students are introduced to the three traditional games